Assessing the seriousness of cybercrime: The case of computer misuse crime in the United Kingdom and the victims’ perspective - Button, Mark (Criminology & criminal justice, 2025)
The reform of the Crime Survey of England and Wales (a national victim survey) has exposed a very high number of individuals who fall victim to computer misuse cybercrimes such as hacking, computer viruses and ransomware. These crimes receive very little attention from the criminal justice system and very few are brought to justice, partly because of the nature of them (global crimes), but also because of a lack of capability among the police. This paper draws on official statistics, an empirical survey and interview research with computer misuse victims. The paper juxtaposes the low priority and lack of resources given to this crime by political and police leaders against many victims’ perceptions and experiences of the crime as equivalent if not more serious than physical counterparts such as burglary, where there is greater interest. The increasing prominence of the virtual world in human life and the impacts of these crimes call for a reappraisal of the official assessment of seriousness in order to raise the priority and increase the capacity of criminal justice towards such offences.